STRUCTURAL AND FUNCTIONAL CHARACTERISTICS OF THE SYNOVIAL MEMBRANE OF THE KNEE JOINT IN OSTEOCHONDROSIS OF THE KNEE JOINT (Universal International Scientific Journal, 2026)
The aim of the study was to investigate morphological and functional changes in the synovial membrane of the knee joint in patients with osteochondrosis of the knee joint (OCKJ). A comprehensive analysis of microscopic changes in synovial tissue, an assessment of inflammatory and destructive processes, and a correlation of structural changes with clinical manifestations of the disease were conducted.
Keywords: synovial membrane; knee joint; osteochondrosis